السعادة الدراسية لدى طلبة الجامعة: Academic well-being among university students - Janabi, Hammadi; ا.م.د. عبد الله مجيد حميد العتابي (Journal of College of Education, 2023)
AbstractThe current research aims to identify:1-The degree of academic well-being among university students                                                                             2-Identify the statistically significant differences in academic well-being according to the sex variables (male, female) and specialization (scientific, human). The current research sample included (400) male and female students of the university from the first and fourth stages of the academic year (2020/2021).                     In order to achieve the objectives of the research, the researcher adopted the relational descriptive research methodology, and the researcher also constructed the (Academic well-being Scale) after reviewing a number of literature and previous studies consisting of (30) paragraphs, which became (26) paragraphs after presenting them to the arbitrators, and the researcher calculated the psychometric characteristics. The validity was calculated using the method of: the apparent honesty and the sincerity of the construction, and the validity was also verified by the method: the Vackronbach method, and the value of consistency was (0.87) . The researcher applied the scale electronically to the research sample and after collecting the results and treating them statistically, where the researcher used the T-test for one sample, and for two independent samples to calculate the discriminative strength, the Pearson correlation coefficient, the Point Bicerial correlation coefficient, the Binary Variance Analysis test, and the zonal test, and the study reached To a number of recommendations and proposals